Cellulosic ethanol from rice straw - Magallanes, Juniper V., et al. (Miagao, Iloilo, Philippines SOTECH, UPVisayas, 2012)
Due to the increasing demand for biofuels and the abundance of raw material in the country, the concept of cellulosic ethanol plant using rice straw was conceptualized.
Sotech thesis-Plant Design
Keywords: Rice straw; Cellulosic ethanol